EPIZOOTOLOGICAL FEATURES OF MANIFESTATION OF INFECTIOUS ENTERITIS OF DOGS IN THE CONDITIONS OF KAMIANETS-PODILSKYI DISTRICT - Prosyanуi S.B.; Horiuk, V.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2021)
In recent years, there has been an increase in cases of dogs with signs of diarrhea not only in Ukraine but also in the world. Meanwhile, clinical and epizootological features of infectious enteritis of dogs in Ukraine require constant monitoring due to the dynamics of the epizootic process associated with increasing numbers and concentrations of animals in a limited area (kennels, animal shelters), changes in breed composition and many other factors. Therefore, the chosen direction of research is relevant. The aim of work is to investigate the spread of the main pathologies of dogs of infectious and non-infectious etiology in the territory of Kamianets-Podilskyi District and to find out some epizootological features of the course of infectious enteritis of dogs in this region. Clinical-anamnestic and pathological data, mycological, bacteriological, serological research methods were taken into account when making the diagnosis. Epizootological features of the manifestation of infectious enteritis in dogs were studied taking into account the incidence rate, seasonality of outbreaks and age susceptibility of animals. When conducting comprehensive diagnostic studies in many regions, it was found that internal non-communicable diseases in dogs are 33.9%, and infectious diseases – 29.3%. Among infectious pathologies, viral infections (25.0%), mycoses (20.2%) and arachnoentomoses (17.7%) were quite often registered. The analysis of infectious diseases revealed a significant percentage of dogs with infectious gastroenteritis – 32.9%, with the majority of dogs (79.3%) suffering from infectious enteritis at the age of 2 to 12 months. There is no clear relationship between the manifestation of infectious enteritis in dogs depending on the time of year. Slightly higher incidence was found in summer (31.3%). The obtained results will further optimize the elimination and preventive measures for the spread of infectious pathology in dogs, in particular viral enteritis.